CRISE E REESTRUTURAÇÃO DO AGRIBUSINESS DO CACAU - Gomes , Andréa da Silva; Machado, Gustavo Bittencourt; Silva , Roberto Sá da; Couto, Vitor de Athayde (Revista Econômica do Nordeste, 1997)
Acervo histórico